Bimbingan Teknis dan Pengawasan Pembangunan Gedung Madrasah Hidayatul Atfal Desa Langon Kecamatan Ponggok, Kabupaten Blitar - Achendry M Kurniawan; Udi Subagyo; Sugeng Riyanto; Rif'atul Khusniah; Johanes Asdhi Purwanto (Universitas Muria Kudus, 2022)
Madrasah Diniyah Hidayatul Atfal building construction began in 2021 until today. However, the construction project has been delayed several times due to some technical issues taking place on the construction site. The first technical issue is that the project was started without any blueprint. As a consequence, the construction workers did not have any reference on how to execute the project. Secondly, it did not have any budget plan either. As a result, there were some building materials left unused. The last is the local community working as construction workers have very limited knowledge on building construction.A civil engineer, particularly an experienced one, is the most suitable solution to overcome those technical issues. Well-experienced civil engineer is able to draw a blueprint, plan budget correctly, identify building materials needed and how much time it takes to complete a construction project. In addition, he can provide assistance for those construction workers during the project. With the help of civil engineer, it is expected that Madrasah Diniyah Hidayatul Atfal construction project can be executed well and is completed in a timely manner.